2008
DOI: 10.1177/1358863x07086191
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulants and non-cardioembolic stroke prevention

Abstract: The use of anticoagulants for secondary prevention following noncardioembolic ischemic stroke is controversial. This systematic review evaluates the safety and efficacy of oral anticoagulation compared with control and antiplatelet therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…20 Furthermore, it has been shown that the NIHSS score predicts the likelihood of recovery after stroke. 21 Accordingly, in our study, cardioembolic strokes were associated with a higher admission NIHSS (median 8.5 [IQR: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] vs. 3 [1][2][3][4][5][6][7][8], p < 0.001). However, we did not find an association of stroke etiology and likelihood of favorable outcome.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…20 Furthermore, it has been shown that the NIHSS score predicts the likelihood of recovery after stroke. 21 Accordingly, in our study, cardioembolic strokes were associated with a higher admission NIHSS (median 8.5 [IQR: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] vs. 3 [1][2][3][4][5][6][7][8], p < 0.001). However, we did not find an association of stroke etiology and likelihood of favorable outcome.…”
Section: Discussionmentioning
confidence: 56%
“…From the total of 230 patients included in this study, 150 (65.2%) had a cardioembolic stroke (AF without other competing mechanism). Compared to patients with stroke of undetermined mechanism, cardioembolic stroke patients had more severe strokes with median NIHSS scores, 3 (1-8) versus 8.5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) respectively, and were more commonly treated with reperfusion therapies: intravenous tissue plasminogen activator (IV tPA), 8.0 versus 2.5%, and mechanical thrombectomy (MT) 14.0 versus 3.8%, respectively (►Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations